Pathomorphological pecularities of the structure of the fetus ovaries from the mothers with placental dysfunction - L. S. Kupriyanova (Zaporožskij Medicinskij Žurnal)
Aim. Placental dysfunction not only leads to fetus adaptive responses, but also causes pathological changes in fetal tissues and organs. In order to identify the pathological features of the structure ovaries of the 22 dead fetuses in utero were studied.